2022
DOI: 10.1080/07853890.2022.2110277
|View full text |Cite
|
Sign up to set email alerts
|

The association between non-alcoholic fatty liver disease (NAFLD) and advanced fibrosis with blood selenium level based on the NHANES 2017-2018

Abstract: Background & Objective Selenium was one of the essential trace elements that played a pivotal role in human health. Although previous studies have investigated the relationship between selenium and non-alcoholic fatty liver disease (NAFLD) and fibrosis, these findings were still inconclusive. Our study was aimed to explore the association between blood selenium level and NAFLD and advanced liver fibrosis diagnosed by vibration controlled transient elastography (VCTE) in US adults. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…viral hepatitis and overdose of alcohol) [22]. Viral hepatitis was defined by the presence of HCV-RNA and/or confirmed hepatitis C antibodies (hepatitis C virus) or the hepatitis B surface antigen (hepatitis B virus) [15]. Overdose alcohol was indicated if >30 g/day for men and >20 g/day for women [15].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…viral hepatitis and overdose of alcohol) [22]. Viral hepatitis was defined by the presence of HCV-RNA and/or confirmed hepatitis C antibodies (hepatitis C virus) or the hepatitis B surface antigen (hepatitis B virus) [15]. Overdose alcohol was indicated if >30 g/day for men and >20 g/day for women [15].…”
Section: Methodsmentioning
confidence: 99%
“…The NHANES is a continuous cross-sectional survey conducted by the National Center for Health Statistics (NCHS) for the assessment of health and nutritional status among the general public of the USA, which included unbiased demographics, dietary, examination, laboratory and questionnaire data. The NHANES has become a frequent database used to study MAFLD or NAFLD because of recently available data on FibroScan liver steatosis assessment [12][13][14][15]. The study cohort was obtained from the NHANES database (2017-2018).…”
Section: Data Source and Study Populationmentioning
confidence: 99%
“…Thus, the therapeutic effect of selenium supplementation on MAFLD may be partly achieved by inhibiting ferroptosis. However, epidemiologic evidence about the association between blood selenium levels and MAFLD appears to be contradic-tory [262][263][264]. Given the unique features of selenium, it is an attractive avenue to explore the role of selenium in MAFLD pathogenesis.…”
Section: Selenium Metabolism and Mafldmentioning
confidence: 99%
“…Studies have shown that lower blood selenium levels are associated with a higher incidence of advanced liver fibrosis ( 151 ). Conversely, higher blood selenium levels (above ~130 μg/L) have been positively correlated with both MAFLD and ghrelin, indicating a dose–response relationship ( 150 , 152 ).…”
Section: Minerals and Mafldmentioning
confidence: 99%